2020
DOI: 10.1002/ijc.32906
|View full text |Cite
|
Sign up to set email alerts
|

Iron intake, oxidative stress‐related genes and breast cancer risk

Abstract: Iron has been suggested to contribute to breast cancer development through oxidative stress generation. Our study investigated associations between iron intake and breast cancer risk, overall and by menopausal and estrogen receptor/ progesterone receptor (ER/PR) status, and modification by oxidative stress-related genetic polymorphisms (MnSOD, GSTM1 and GSTT1). A population-based case-control study (3,030 cases and 3,402 controls) was conducted in Ontario, Canada. Iron intake (total, dietary, supplemental, hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…Consistent with other preclinical reports, effects were modest and not statistically significant [ 47 ]. More importantly, the data were consistent with three population studies published between 2019 and 2021 [ 6 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Specifically, we evaluated the data ( Table 5 ) in a manner that paralleled the common approach in epidemiology, contrasting low versus high iron status, i.e., by comparing groups 1–3 vs. 4–7: the cancer incidence was 63.3 vs. 70.0 (RR = 1.10 (0.95, 1.20; p = 0.098)).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with other preclinical reports, effects were modest and not statistically significant [ 47 ]. More importantly, the data were consistent with three population studies published between 2019 and 2021 [ 6 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Specifically, we evaluated the data ( Table 5 ) in a manner that paralleled the common approach in epidemiology, contrasting low versus high iron status, i.e., by comparing groups 1–3 vs. 4–7: the cancer incidence was 63.3 vs. 70.0 (RR = 1.10 (0.95, 1.20; p = 0.098)).…”
Section: Resultssupporting
confidence: 88%
“…Recently reported results from population studies, systematic reviews, and meta-analyses revealed no relationship between iron status and breast cancer, a weak positive association, or a small protective effect of low iron status [ 6 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. However, in most of those studies, the authors concluded that further investigation was merited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A European randomized controlled study showed there was a positive association between serum transferrin level and the incidence of ER- breast cancer ( Hou et al, 2021 ). A Canadian cohort study showed that dietary iron supplementation was associated with a low risk of breast cancer, and heme iron was positively related with the risk of the ER and or PR positive breast cancer subtypes in postmenopausal women ( Chang et al, 2020 ). High ferroportin and hepcidin expression play a protective role in patients with breast cancer ( Pinnix et al, 2010 ).…”
Section: Iron and Iron-regulatory Proteins Involved In Breast Cancermentioning
confidence: 99%
“…Oxidative stress may be associated with the estrogen/progesterone receptor status of the tumor [10,17] and may persist for up to 6 months post tumor removal in women with breast cancer [18]. DNA repair enzymes help maintain stability in the genome, and malfunctions in DNA repair pathways are linked to the progression and development of breast cancer [19].…”
Section: Introductionmentioning
confidence: 99%